A cost comparison of introducing and delivering pneumococcal, rotavirus and human papillomavirus vaccines in Rwanda. Issue 51 (16th December 2015) - Ngabo, Fidèle; Levin, Ann; Wang, Susan A.; Gatera, Maurice; Rugambwa, Celse; Kayonga, Celestin; Donnen, Philippe; Lepage, Philippe; Hutubessy, Raymond
Abstract: Background: Detailed cost evaluations of delivery of new vaccines such as pneumococcal conjugate, human papillomavirus (HPV), and rotavirus vaccines in low and middle-income countries are scarce. This paper differs from others by comparing the costs of introducing multiple vaccines in a single country and then assessing the financial and economic impact at the time and implications for the future. The objective of the analysis was to understand the introduction and delivery cost per dose or per child of the three new vaccines in Rwanda to inform domestic and external financial resource mobilization. Methods: Start-up, recurrent, and capital costs from a government perspective were collected in 2012. Since pneumococcal conjugate and HPV vaccines had already been introduced, cost data for those vaccines were collected retrospectively while prospective (projected) costing was done for rotavirus vaccine. Results: The financial unit cost per fully immunized child (or girl for HPV vaccine) of delivering 3 doses of each vaccine (without costs related to vaccine procurement) was $0.37 for rotavirus (RotaTeq ® ) vaccine, $0.54 for pneumococcal (Prevnar ® ) vaccine in pre-filled syringes, and $10.23 for HPV (Gardasil ® ) vaccine. The financial delivery costs of Prevnar ® and RotaTeq ® were similar since both were delivered using existing health system infrastructure to deliver infant vaccines at health centers. The total financial cost of delivering Gardasil ® was higher than those of the two infant vaccines due to greater resource requirements associated with creating a new vaccine delivery system in for a new target population of 12-year-old girls who have not previously been served by the existing routine infant immunization program. Conclusion: The analysis indicates that service delivery strategies have an important influence on costs of introducing new vaccines and costs per girl reached with HPV vaccine are higher than the other two vaccines because of its delivery strategy. Documented information on financial commitments for new vaccines, particularly from government sources, is a useful input into country policy dialogue on sustainable financing and co-financing of new vaccines, as well as for policy decisions by donors such as Gavi, the Vaccine Alliance.